The Role of Cultural Heritage Tourism in Regenerating Old Muharraq in Bahrain - Fatima Shubbar; Djamel Boussaa (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The historic city of Muharraq in Bahrain encompasses a unique cultural heritage. Since the discovery of oil in 1932, Old Muharraq started to be abandoned by its original inhabitants who moved to the periphery. Due to neglect, the old houses were decaying and collapsing. In order to prevent further losses, the government launched several rehabilitation projects in Muharraq. The pearling path is one of these significant regeneration projects that will be explored here. This paper focuses on the role of cultural heritage tourism and its implications for urban regeneration in old Muharraq. The methodology used is based on the case study approach. A comprehensive onsite study was carried out to identify the challenges of urban regeneration. In addition, a number of informal interviews were conducted with Bahrain Authority for culture and Antiquities representatives. The paper concludes with a number of recommendations to revive old Muharraq via a sustainable cultural heritage tourism strategy.